Inovasi Administratif dalam Pelayanan Keimigrasian: Menuju Birokrasi Modern dan Responsif - Baghitz Hanan; Virra Wirdhiningsih; Sri Kuncoro Bawono (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
This study examines administrative innovations in immigration services, including e-visa systems, biometric-based autogates, online queue management, and foreigner monitoring dashboards. The findings reveal that these innovations improve service speed, transparency, accountability, and public satisfaction. However, challenges such as limited human resource competencies, ICT infrastructure gaps, data security concerns, and bureaucratic resistance hinder implementation. The study also compares best practices from several advanced countries as references for reform. Recommendations focus on strengthening human resources, infrastructure, data security, and change management to sustain digital transformation in immigration services. Further research is suggested to explore socio-economic impacts and emerging technologies in the context of immigration service delivery.